ORGANIZATION OF FOREIGN LANGUAGE TEACHING IN TECHNICAL UNIVERSITIES - Atabaeva Nodira Djuraevna (European Journal of Humanities and Educational Advancements, 2022)
This article presents an analysis of various methods of teaching a foreign language. The right choice of methodology and approach helps motivate students of non-linguistic specialties and forms an interest in learning foreign languages.